Effect of pre-harvest treatment, packaging and storage conditions on shelf life and quality of lasora (Cordia myxa) fruits - MEGHWAL, P R; SINGH, DALPAT; SINGH, AKATH (The Indian Journal of Agricultural Sciences, 2022)
An experiment was conducted on the effect of pre-harvest spray of calcium chloride (1–2%), pre-cooling, packaging materials and storage conditions on shelf life and quality of lasora fruits. The LDPE bags were found most efficient in reducing the PLW followed by cling film and brown paper bags both under ambient and refrigerated conditions. The pre-cooled fruits revealed significantly lower PLW compared to non pre-cooled fruits up to 4th day in ambient condition and till 14th day in refrigerated conditions. Under ambient conditions, the maximum shelf life of 7 days was recorded in LDPE followed by cling film wrap and brown paper bags while under refrigerated conditions it could be extended up to 14 days in LDPE and cling film packed fruits and 7 days in brown paper. The spoilage was significantly higher at ambient condition within 7 days in LDPE packed fruits (3.54%) and least in cling film. The spoilage increased to 10–12% in refrigerator when the fruits were stored for longer duration and it was not affected significantly by different treatments. The antioxidant activity was absent in the fruits stored in ambient condition while it was recorded in refrigerated fruits even after 14 days of storage.